2017
DOI: 10.31138/mjr.28.3.133
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-steroidal anti-inflammatory drugs on matrix metalloproteinases levels in patients with osteoarthritis

Abstract: The objective of this study is to determine and comparatively evaluate the effects of three different non-steroidal anti-inflammatory drugs on the levels of metalloproteinases MMP-1, MMP-3 and MMP-8, as well as on their tissue inhibitor TIMP-1, in patients suffering from idiopathic osteoarthritis. The effect of these drugs on the articular cartilage and the probable use of MMPs and TIMP-1 as markers of disease and treatment was also investigated. METHODS: Thirty-six patients with OA were selected and allocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…alpha in human chondrocytes. A conducted by Efstathiou et al (2017) on 36 OA patients who were given NSIDs reported that MMP-3 levels were significantly reduced after NSAID treatment [38]. Matrine is an anti-inflammatory, also shown to inhibit IL-1β-induced matrix metalloproteinase expression by suppressing MAPK and NF-B activation in human chondrocytes in vitro.…”
Section: Levels Of Il-1β and Tnf-α With Mmp3 Gene Expression Rs679620mentioning
confidence: 99%
“…alpha in human chondrocytes. A conducted by Efstathiou et al (2017) on 36 OA patients who were given NSIDs reported that MMP-3 levels were significantly reduced after NSAID treatment [38]. Matrine is an anti-inflammatory, also shown to inhibit IL-1β-induced matrix metalloproteinase expression by suppressing MAPK and NF-B activation in human chondrocytes in vitro.…”
Section: Levels Of Il-1β and Tnf-α With Mmp3 Gene Expression Rs679620mentioning
confidence: 99%
“…However, the expression level of MMP-3 also changes along with disease progression and remission, which suggests MMP-3 may be a marker of curative effects. Serum MMP-3 levels in patients with OA were significantly decreased after treatment with non-steroidal anti-inflammatory drugs (Efstathiou and Settas, 2017) and decreased significantly in RA patients treated with certolizumab pegol (Ling et al, 2017). Other studies in which RA patients were treated with methotrexate monotherapy (Kazuko et al, 2016) and AS patients were treated with etanercept (Dongyi et al, 2017) showed similar results to those described above.…”
Section: Clinical Detection and Inhibitors Of Mmp-3 Mmp-3 Detectionmentioning
confidence: 99%
“…All OA group dogs received a non-steroidal anti-inflamatory drug (NSAID) in the first 7-10 days after surgical intervention which may have impacted the results of follow up serum and SF biomarker measurements in this study. A previous study that has evaluated the effect of NSAID use on collagenase and general MMP activity in cartilage, and synovium did not show a significant difference compared to controls despite 8 weeks of use in a tCrCL model [52] In vitro studies have shown a dose-dependent suppressive effect by NSAIDs on MMPs in human synovial fibroblasts and bovine chondrocyte models [53,54] as well as in clinical trials of human knee OA [55]. However, the impact of the suppressive effect of the short term meloxicam used in this study on the serum and SF biomarker measurements at T2 and T3 are unknown.…”
Section: Plos Onementioning
confidence: 99%